Non-alcoholic/Metabolic-Associated Fatty Liver Disease and Helicobacter pylori Additively Increase the Risk of Arterial Stiffness - Choi, Ji Min; Park, Hyo Eun; Han, Yoo Min; Lee, Jooyoung; Lee, Heesun; Chung, Su Jin; Lim, Seon Hee; Yim, Jeong Yoon; Chung, Goh Eun (Frontiers in Medicine, 2022)
BACKGROUND: Nonalcoholic fatty liver disease (NAFLD) and Helicobacter pylori (Hp) infection have a close association with an increased risk of cardiovascular disease. Metabolic dysfunction-associated fatty liver disease (MAFLD) is characterized by metabolic dysfunction in NAFLD. We investigated the synergistic effects of NAFLD/MAFLD and Hp infection on the risk of arterial stiffness in an asymptomatic population. METHODS: We included individuals who underwent abdominal ultrasonography, anti-Hp Ig G antibody evaluations and cardio-ankle vascular index (CAVI) during health screening tests between January 2013 and December 2017. Arterial stiffness was defined using CAVI. A logistic regression model was used to analyze the independent and synergistic effects of NAFLD/MAFLD and Hp infection on the risk of arterial stiffness. RESULTS: Among 3,195 subjects (mean age 54.7 years, 68.5% male), the prevalence of increased arterial stiffness was 36.4%. In the multivariate analysis, subjects with NAFLD but without Hp infection and those with both NAFLD and Hp infection had a signiﬁcantly higher risk of increased arterial stiffness (odds ratio [OR] 1.61, 95% confidence interval [CI] 1.15-2.26, and OR 2.23, 95% CI 1.63-3.06, respectively) than subjects without Hp infection and NAFLD. Regarding MAFLD, Hp infection additively increased the risk of arterial stiffness in subjects with MAFLD (OR 2.13, 95% CI 1.64-2.78). CONCLUSIONS: An interactive effect of Hp infection on the risk of arterial stiffness in individuals with NAFLD/MAFLD was observed. Hp infection additively increases the risk of arterial stiffness in subjects with NAFLD or MAFLD.